2003
DOI: 10.1002/tox.10124
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic exposure to lead on estrogen action in the prepubertal rat uterus

Abstract: Lead is a widely spread environmental pollutant known to affect both male and female reproductive systems in humans and in experimental animals. The present study investigated the effect of a chronic exposure to lead on different parameters of estrogen stimulation in the uteri of prepubertal rats. Chronic exposure to lead enhanced some parameters of estrogen stimulation, inhibited other estrogenic responses, while the remainder were unaltered. Estrogen-induced uterine eosinophilia (24 h), the proportion of ute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 30 publications
4
18
3
Order By: Relevance
“…PbB in these monkeys was approximately 35 μg/dL. Also, a study in rats showed that exposure to lead can enhance some parameters of estrogen stimulation, inhibit other estrogenic responses, and some responses remain unaltered (Tchernitchin et al 2003). In that study, female rats were administered lead acetate every 3 days from age 7 days and until they were 19 days old; the PbB in these rats was approximately 47 μg/dL.…”
Section: Health Effectsmentioning
confidence: 96%
“…PbB in these monkeys was approximately 35 μg/dL. Also, a study in rats showed that exposure to lead can enhance some parameters of estrogen stimulation, inhibit other estrogenic responses, and some responses remain unaltered (Tchernitchin et al 2003). In that study, female rats were administered lead acetate every 3 days from age 7 days and until they were 19 days old; the PbB in these rats was approximately 47 μg/dL.…”
Section: Health Effectsmentioning
confidence: 96%
“…This dissociation was reported under several experimental conditions in the rat uterus. 7,8,12,13 The lower incidence of breast cancer in Asian women than in western women, 14 which parallels the higher amount of phytoestrogens (including soybean products) consumed by Asian women, 14 was attributed to lifestyle but not to genetic factors. 15,16 In fact, in East and Southeast Asia, the average intake of phytoestrogens is estimated to be more than 10 times higher than in the United States or Europe, 17 and plasma isoflavone concentrations are higher in Japanese women than in Europeans.…”
Section: Introductionmentioning
confidence: 91%
“…The various parameters of estrogen stimulation were evaluated at the times during which their maximal response to E 2 occurs. 22,44,45 Uterine eosinophilia reaches maximal response at 6 or 24 h; endometrial edema reaches maximal response at 6 h and declines thereafter; and uterine luminal epithelial, stromal, and myometrial cell proliferation reaches maximal level responses at 24 h after hormone treatment. To allow a comparison between the effects of daidzein among the different parameters of estrogen stimulation, all responses were expressed as % of response to E 2 , that is, the value of vehicle-treated animals was considered 0% response, and the value of response to E 2 -100% response.…”
Section: Quantification Of Estrogenic Responsesmentioning
confidence: 99%
“…42,43 Cell hypertrophy (increase in cell size) was evaluated morphometrically in the above cell-types. 22,33,42,44 Human breast cancer cell culture procedure…”
Section: Quantification Of Estrogenic Responsesmentioning
confidence: 99%
See 1 more Smart Citation